2018
DOI: 10.2478/amcs-2018-0015
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale hyperspectral image compression via sparse representations based on online learning

Abstract: In this study, proximity based optimization algorithms are used for lossy compression of hyperspectral images that are inherently large scale. This is the first time that such proximity based optimization algorithms are implemented with an online dictionary learning method. Compression performances are compared with the one obtained by various sparse representation algorithms. As a result, proximity based optimization algorithms are listed among the three best ones in terms of compression performance values fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Can reconstruct the original real values of pixels. 75 GIST, SpaRSA, 76 spectral-spatial adaptive sparse representation (SSASR), 77 and TwIST. 76 Technique.…”
Section: Cnn-ntd 31mentioning
confidence: 99%
See 1 more Smart Citation
“…Can reconstruct the original real values of pixels. 75 GIST, SpaRSA, 76 spectral-spatial adaptive sparse representation (SSASR), 77 and TwIST. 76 Technique.…”
Section: Cnn-ntd 31mentioning
confidence: 99%
“…75 GIST, SpaRSA, 76 spectral-spatial adaptive sparse representation (SSASR), 77 and TwIST. 76 Technique. Sparse coding is used by multiple algorithms in different style,and a generalized and in-depth description of the technique is given in Fig.…”
Section: Cnn-ntd 31mentioning
confidence: 99%
“…Using dictionary learning in the lossy hyperspectral image compression algorithms is quite common [18,38,40]. In the literature [36,37], it is shown that online dictionary learning algorithm is more effective in processing large datasets with sequentially arriving samples such as hyperspectral images. This sparse representation process finds the sparsest solution, which means solving the non-deterministic polynomial-time hard (NP-hard) 0 -norm minimization problem [10].…”
Section: Introductionmentioning
confidence: 99%